Assessing the effectiveness of agricultural conservation practices in maintaining soil organic carbon under contrasting agroecosystems and a changing climate. Issue 5 (26th May 2021) - Gollany, Hero T.; DelGrosso, Stephen J.; Dell, Curtis J.; Adler, Paul R.; Polumsky, Robert W.
Abstract: The potential of conservation practices to maintain soil organic C (SOC) and reduce climate change impacts on yields is unknown. This study aimed to validate the DayCent model with observed yield data and the CQESTR model with measured SOC in two agroecosystems, and predict the best practices to sustain SOC under projected climate change. Data were from a conventional tillage (CT) wheat ( Triticum aestivum L.)–fallow rotation without N or with 135 kg N ha –1 fertilizer, and no‐till (NT) experiments, NTA (NTA0 W‐F and NTA135 W‐F) and NTB with a wheat–pea ( Pisum sativum L.) cover crop (NTB0 W‐P and NTB135 W‐P) in Oregon; and crop rotations with CT and NT silage or grain corn (Zea mays L.)–soybean [Glycine max (L.) Merr.]–alfalfa ( Medicago sativa L.) with or without manure or stover removal or a cover crop in Pennsylvania. Measured and CQESTR‐simulated SOC were significantly ( p < .0001) correlated ( r = .90). In Oregon, predicted SOC to 60 cm increased under NTA135 W‐F and NTB135 W‐P at 0.05 and 0.08 Mg ha –1 yr –1 under projected climate change, respectively. The NT management under dryland production provided a limited SOC increase. In Pennsylvania, predicted SOC to 1 m decreased at 0.07 Mg ha –1 yr –1 in corn–soybean under CT or NT with stover removal, but increased by 0.71 Mg ha –1 yr –1 in dairy forage NT and manure added under climate change. The responses of SOC to climate change were affected by management, biomass type, edaphic properties, local climate, and agroecosystem. Core Ideas: Wheat–fallow + NT cannot sustain SOC unless wheat yields increase under climate change Wheat–cover crop + NT increased SOC under current and projected Mediterranean climate Dairy forage under NT with or without manure are more resilient practices than corn–soybean Additional biomass inputs were required to sustain SOC with stover removal under RCP8.5 At both sites, NT with N fertilizer, a cover crop, and manure or recalcitrant C sustained SOC